2022
DOI: 10.1371/journal.pone.0277650
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the risk of transfusion-transmitted infectious disease markers in blood and blood component donations: Movement from remunerated to voluntary, non-remunerated donations in Lithuania from 2013 to 2020

Abstract: Lithuania has a long history of remunerated donations. The first steps towards voluntary, non-remunerated blood and blood component donations started in 2004. Lithuania achieved 99.98% voluntary non-remunerated donations (VNRDs) in 2020. This study aimed to assess the risk of transfusion-transmitted infectious (TTI) disease markers for remunerated donations in comparison with VNRDs in Lithuania from 2013 to 2020. Data were obtained from the Lithuanian Blood Donor Register. The prevalence was calculated as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Tis may be attributed to continuous measures taken by the blood services in Zhejiang Province to prevent the spread of HIV in recent years. Blood services can efectively reduce the number of HIV-infected individuals among blood donors through measures such as improving public awareness and understanding of blood donation and blood safety, as well as self-exclusion of blood donors [28][29][30]. Other contributing factors include the low HIV prevalence in Zhejiang Province and a decreasing HIV infection rate among the general population since 2020 (https://www.cdc.zj.cn/).…”
Section: Discussionmentioning
confidence: 99%
“…Tis may be attributed to continuous measures taken by the blood services in Zhejiang Province to prevent the spread of HIV in recent years. Blood services can efectively reduce the number of HIV-infected individuals among blood donors through measures such as improving public awareness and understanding of blood donation and blood safety, as well as self-exclusion of blood donors [28][29][30]. Other contributing factors include the low HIV prevalence in Zhejiang Province and a decreasing HIV infection rate among the general population since 2020 (https://www.cdc.zj.cn/).…”
Section: Discussionmentioning
confidence: 99%
“…Monetary incentives for blood donors may crowd out altruistic motivations, exploit vulnerable donors [2] and jeopardize blood safety [29] because they might decrease donor compliance with eligibility criteria that determine whether the donation is safe for donor and patient.…”
Section: Ethical Considerations and Final Remarksmentioning
confidence: 99%
“…The ethical question of whether it is desirable to offer incentives for what we often consider an act of altruism and solidarity has repeatedly been raised [24–27], with arguments against donor compensation showing limited basis in scientific evidence [26, 28]. Monetary incentives for blood donors may crowd out altruistic motivations, exploit vulnerable donors [2] and jeopardize blood safety [29] because they might decrease donor compliance with eligibility criteria that determine whether the donation is safe for donor and patient. However, improved testing for infectious disease markers has developed and improved such that infections in transfusion recipients, while not absent, have been minimized.…”
Section: Ethical Considerations and Final Remarksmentioning
confidence: 99%
“…Within Lithuania, blood and blood components donations shifted from mostly remunerated to mostly VNRD due to national programmes promoting VNRD following Lithuania's EU membership [15]. A study examining this unique within‐country natural experiment showed higher prevalence of transfusion‐transmitted infectious (TTI) disease markers for remunerated donations compared to donations based on VNRD from 2013 to 2017 [15]. This is consistent with previous research that found lower TTI disease markers for voluntary compared to paid donors in the Democratic Republic of Congo [16] and Nigeria [17].…”
Section: Higher Safety For Donors and Donated Productsmentioning
confidence: 99%